(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
The rapid expansion of digital globalization has fundamentally transformed social interactions, cultural communication, and individual value systems, creating both new opportunities and significant challenges for personal spiritual development. This article examines the contemporary trends in enhancing individual spirituality within the context of digital globalization from a socio-philosophical perspective. It analyzes the influence of digital technologies, social media, artificial intelligence, and virtual communication on moral consciousness, cultural identity, and spiritual values. Particular attention is devoted to the interaction between technological progress and traditional ethical principles, highlighting the need to preserve cultural heritage while adapting to the realities of the digital age.